Recommendations for Сonstruction of Inclusive Environment at Activities with Participation of People with ASD - Steinberg A.; Voskov A. (Moscow State University of Psychology and Education, 2018)
Construction of inclusive environment for people with autism, including activities with their participation, is an actual task, but its implementation is complicated by that fact that required measures are not evident. In the article sensory and communicative issues, routines and stereotyped behaviour among people with ASD are discussed. And relevant recommendations for construction of inclusive environment for people with ASD at different activities.